Gel growth and characterization of Cs3Bi2Br9 perovskite single crystals for radiation detection - Alshogeathri, Saqr; Cao, Da; Kim, Doup; Yang, Ge (Frontiers in Physics, 2023)
Metal halide perovskites have been sought for ionizing radiation detection due to their tunable bandgap, high quantum yield, high absorption coefficient, excellent charge transport properties, flexible chemistry synthesis and cost-effective manufacturing. Among the family of perovskites, bismuth-based halide perovskites have attracted a rapidly growing interest as possible alternatives to lead-based halide perovskites in the development of nontoxic perovskites for opto-electronic devices. Herein, bismuth-based inorganic perovskite Cs3Bi2Br9 single crystals were successfully grown using an innovative dual-diffusion gel growth technique for the first time. Silica gel has been developed as an enabling medium for gel growth of single crystals due to its transparency and easy control of nucleation sites. The UV-vis transmission spectrum was recorded using a light source of deuterium and halogen lamps and a Tauc plot was obtained, which gave an estimate of the bandgap energy, 2.55 eV. Silver electrodes were used on the top surface and the bottom surface of Cs3Bi2Br9 single crystals for material characterization and detector tests. Current-voltage (I-V) measurements gave a room-temperature resistivity of 1.79 × 〖10〗^11 Ω•cm. The Cs3Bi2Br9 single crystals were then tested for X-ray response using ONtesting which revealed attractive responsiveness for X-ray photons (rise and fall time: ≈0.3 s ). Using the net current (I_(X_ray )-I_dark), which can be extracted from the X-ray response measurements at varied applied voltages, a modified Hecht fitting was applied to estimate the mobility-lifetime product of electrons, μτ=5.12×〖10〗^(-4) ±6.70 × 〖10〗^(-5) cm^2/V for a Ag/Cs3Bi2Br9/Ag device. This study shows that our innovative crystal growth method, enabled by the unique gel growth process, can be used as an appealing technique to grow functional crystals for opto-electronic devices. Meanwhile, Cs3Bi2Br9 has shown great potential as a promising candidate for X-ray detection applications. Our efforts serve as a metric for growing halide perovskites in the gel for opto-electronic devices.